Praktik Green Financing pada Bank Pembiayaan Rakyat Syariah: Pendekatan Sustainability Accounting Standards Board - Elfadhli Elfadhli; Gampito Gampito; Revi Candra; Sri Madona Saleh; Lili Ramahdani (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study examines the implementation of Green Financing in Islamic Rural Bank in West Sumatra using the Sustainable Accounting Standards Board (SASB) Index as an analytical framework. A descriptive qualitative approach was employed, utilizing interviews and surveys to evaluate Environmental, Social, and Governance (ESG) dimensions. The findings indicate that environmental initiatives have been initiated; however, their implementation remains informal and lacks systematic documentation. In contrast, the social dimension demonstrates a strong commitment to employee welfare and community empowerment, reflecting the social objectives inherent in Sharia banking principles. Meanwhile, the governance dimension shows that environmental risk considerations have been partially integrated into standard operating procedures (SOP), aligned with Sharia compliance requirements. Overall, the results suggest that while Islamic Rural Bank practices are generally consistent with basic SASB standards, the absence of comprehensive written policies and standardized reporting mechanisms limits the effectiveness and sustainability of green financing implementation. This study highlights the need for formalized governance structures and documented environmental policies to strengthen sustainable finance practices within Islamic rural banking institutions